OPTIMIZATION OF ADSORPTION OF CONGO RED DYE FROM AQUEOUS SOLUTION WITH ACTIVATED CARBON FROM CASTOR SEED SHELL USING CENTRAL COMPOSITE DESIGN - Ohikere, Hussaina Ize; Yashim, Z. I.; Nwokem, N. C. (FUDMA Journal of Sciences, 2023)
The present research highlighted the efficacy of activated carbon from castor seed (ACCS) for the removal of Congo red dye from aqueous solution through batch study. Central–Composite Design (CCD) by response surface methodology was used to optimize the adsorption process. Based on CCD design, the quadratic models were developed co-relating the adsorption variables to the removal efficiency. Analysis of variance (ANOVA) was incorporated to judge the adequacy of the model. Fourier Transform Infrared (FTIR) analysis was carried out on ACCS to reveal the functional groups which aided the adsorption of Congo red dye. The model predicted the optimized conditions as follows: initial concentration (100.0 mg/L), adsorption dose (1.2 g), contact time (45.0 mins) and pH (4.0) which resulted to a 99.97% removal efficiency of Congo red dye. Therefore, the present results demonstrate that ACCS is a low-cost alternative for the removal of Congo red dye from aqueous solution.
Keywords: Castor seed; adsorption; Congo red dye; Activated carbon